Assessment of safety level in performing building maintenance work in Malaysia - Ismail, Ilyani (2006)
Buildings are expected to exist for a long time, whether or not they are actually designed to achieve such longevity. The task of operating, maintaining and improving this stock of existing building is the responsibility of the building industry, as much as the production of new buildings. In many ways, it presents a more demanding safety consideration in performing the building maintenance work. Hence, in order to know more on safety consideration in performing building maintenance work, a survey in distributed among 100 building maintenance contractor in Kuala Lumpur, Selangor and Johor Bahru. The survey consists of general information and 28 safety factors relevant to contractor safety which were used to measure the contractor’s safety attitude. Finally, the safety factors were ranked by their level of importance based on the survey result. In addition, the frequency rates and contractors safety attitudes determinants were used to measure the safety performance level for building maintenance contractors.